Clinically isolated lesions of the type seen in multiple sclerosis: a cognitive, psychiatric, and MRI follow up study. - Feinstein, A (1992)
There is a dearth of longitudinal studies on psychometric and psychiatric change in multiple sclerosis (MS) particularly on the evolution of these abnormalities early in the disease process. A 4 1/2 year follow up study documenting magnetic resonance imaging (MRI), psychometric, and psychiatric abnormalities was undertaken in a group of 48 patients with clinically isolated lesions--for example, optic neuritis--which are frequently the harbinger of MS. At follow up about half the subjects had developed clinically definite MS, with memory deficits becoming apparent. Deficits in attention documented at initial assessment were present but unchanged in those subjects who still had a clinically isolated lesion status. However, after MS was categorised into a relapsing-remitting or chronic progressive course, patients with a chronic progressive course were found to have significantly deteriorated with regard to auditory attention tasks. T1 relaxation times in apparently normal white matter correlated with certain indices of cognitive impairment. In developing a model to explain the pathogenesis of intellectual and emotional change in MS, the interaction of organic, psychological, and social factors needs to be emphasised.